Successful umbilicus salvage following concurrent infraumbilical single-port myomectomy and free transverse rectus abdominis myocutaneous flap elevation: a case report - Jinhyun Kim (Korean Society for Aesthetic Plastic Surgery, 2021)
Performing a concurrent gynecologic operation and mastectomy with immediate breast reconstruction using a free transverse rectus abdominis myocutaneous flap may increase the risk of complications such as umbilical necrosis due to vascular compromise. Imaging studies such as preoperative computed tomography angiography and intraoperative indocyanine green testing can provide information regarding the umbilical blood supply, facilitating decision-making for pedicle selection. Therefore, in situations where a coordinated operation is unavoidable, a thorough preoperative and intraoperative evaluation of the umbilical blood supply is recommended to avoid complications.